Penerapan Sistem Pendidikan dan Kurikulum di Akademi Militer Tangerang - Zamin Zatua; Ana Nurhasana (CV. ULIL ALBAB CORP, 2026)
This study to find out the facts of the background of the formation of the Tangerang Military Academy in 1945-1946, the education pattern at the Tangerang Military Academy from 1945-1946 and the reasons for the closure of the Tangerang Military Academy in 1946. The method used in this study is the historical method, including heuristics (data collection), source criticism, interpretation, and historiography. The results of this study indicate that the Tangerang Military Academy is an emergency military academy established on November 18, 1945 which aims to produce cadres who will fill vacant positions in the regiment. The education pattern at the Tangerang Military Academy is almost the same as the education pattern for prospective Peta shodancho during the Japanese era because the trainers or teachers there were former Peta soldiers. In March 1946, the Tangerang Military Academy was closed because the trainers and teachers felt that the Tangerang Military Academy was no longer needed. So the Tangerang Military Academy only produced one class.